Accounting for combustion mode switch dynamics and fuel penalties in drive cycle fuel economy. (April 2016) - Nüesch, Sandro; Gorzelic, Patrick; Jiang, Li; Sterniak, Jeff; Stefanopoulou, Anna G
A methodology is introduced to analyze the drive cycle fuel economy of a vehicle equipped with a multimode combustion engine, utilizing commercial cam phasers and two-step cam profile switching. The analysis is based on a longitudinal vehicle model with manual transmission. The engine model employs a finite state machine describing mode switches between two distinct combustion modes, namely, spark-ignited and homogeneous charge compression ignition. Preliminary combustion mode switch experiments were used to parameterize the model. The influence of mode switch fuel penalties on drive cycle fuel economy was quantified through application of the model to the federal test procedure (FTP-75), the highway fuel economy test (HWFET) and the US06 supplemental federal test procedure. The mode switches were analyzed individually in terms of their benefit on fuel economy and a distinction was made between harmful and beneficial mode switches. Mode switches were defined as harmful whether their fuel penalty is greater than the benefits originating from spending time in the subsequent homogeneous charge compression ignition mode. A parametric study was conducted to investigate the impact of harmful mode switches on fuel economy as a function of the fuel penalties during the switch. In the case of high fuel penalties, supervisory control becomes an important tool for minimizing the number of harmful mode switches. One possible supervisory strategy discussed is a smoothing strategy, in which a mode switch is delayed by introducing a dwell time.